Electrophysiological Studies on the Impact of Repeated Electroconvulsive Shocks on Catecholamine Systems in the Rat Brain - Tsen, Peter (Université d'Ottawa / University of Ottawa, 2011)
Electroconvulsive therapy (ECT) effectively treats depression by administration of repeated seizure-inducing electrical stimuli. Sprague-Dawley rats were administered 6 electroconvulsive shocks (ECS) over 2 weeks, and in vivo single unit extracellular electrophysiological activity was recorded after 48 hours. Overall firing activity in the locus coeruleus and ventral tegmental area was unchanged, suggesting the therapeutic efficacy of ECT may not be attributed to increased norepinephrine and dopamine release. There were more spontaneously active neurons in the substantia nigra pars compacta (SNc), indicating greater dopamine tone in the nigrostriatal motor pathway, which may contribute to alleviation of psychomotor retardation. In the facial motor nucleus (FMN), locally administered norepinephrine, but not serotonin, facilitated greater glutamate-induced firing, which may contribute to improved facial motricity. Current results indicate that repeated ECS enhances postsynaptic norepinephrine neurotransmission in the FMN and SNc dopamine neurotransmission, which could represent the mechanism behind the alleviation of depressive symptoms including psychomotor retardation.
Keywords: depression; ECT; electroconvulsive; ECS; antidepressant; electrophysiology; serotonin; dopamine; norepinephrine; facial; motor; nigra; psychomotor; electroshock